Pengaruh Metode SQ3R dalam Pembelajaran Maharah Al-Qira'ah di Kelas VIII MTs An-Nizomiyah Tebo Jambi - Yulva Maya Padilah; Putri Aldina Fahira (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This research discusses learning Arabic, especially maharah al-qira'ah, using the SQ3R method. The aim of this research is to determine the effect of the SQ3R method in learning maharah al-qira'ah in class VIII at MTs An-Nizomiyah Tebo Jambi. This type of research is quantitative research with an experimental approach with a quasi experimental design. Data collection techniques used were tests, observation and documentation. The data analysis technique uses the t-test, but before carrying out the t-test, the researcher used SPSS 29 for the normality test and homogeneity test, because the data must be normal and homogeneous. The results of learning maharah al-qira'ah for class VIII students at MTs An-Nizomiyah Tebo Jambi using the SQ3R method in the experimental class before using the SQ3R method were 54.5769 and after using it were 84.3077. Based on the analysis of test results in the experimental chapter, the t-test shows a calculated